A STUDY OF GRAMMATICAL ERRORS IN SKRIPSI ABSTRACT ON UNDERGRADUATE EFL STUDENTS - nunuk indah mayangsari (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2019)
AbstractThe aim of this article is to know common grammatical errors made by EFL students in their skripsi abstract. This present study analysed the grammatical errors in abstract of skripsi by consideration that the students were English Department of Unisma. It indicates that they have been taught English grammar for four semester. This study was designed to be an exploratory sequential mixed method approach. The data were taken from skripsi abstracts and analysed into identification, classification, and description of errors by using tabulation. To collect the data, the researcher used the simple random sampling method from the latest three years (2016, 2017, 2018) . To achieve an available data, the researcher classified the errors according to the Dulay’s surface strategy taxonomy theory (omission, addition, misformation, and misordering). The finding of this study showed that there were 114 errors to which divided into 66 errors of omission (57.89%), 8 errors of addition (7.02), 34 errors of misformation (29.82%), and 6 errors of misordering (5.26%). Keywords: Grammatical error, skripsi abstract, omission, addition, misformation, misordering.